EVALUASI BANTUAN PROGRAM UPPO (UNIT PENGOLAHAN PUPUK ORGANIK) PADA KELOMPOK TANI DI KABUPATEN SOLOK - SUMATERA BARAT - Firdaus; arfai; Jaswandi (Wahana Peternakan, 2023)
This study aimed to determine the inputs given, the process of implementing the UPPO program, and the results of the UPPO program in Solok Regency. Respondents in the study were Farmer Groups who received assistance from the Organic Fertilizer Processing Unit (UPPO) program in 2017, namely the Kelompok Tani Hulu Gawan, Kandih Maju Bersama, dan Kelompok Tani Sawah Rambahan. The method that we used in this study is a survey method. The observed variables are inputs  and outputs of implementation of the UPPO program. The results of this study indicate that the inputs for the UPPO program assistance carried out by the research farmer groups are match accordance with the technical instructions for processing organic fertilizers. The livestock breeds used were Simmenal Cattle, Ongole Crossbreed, Limousin and Coastal Cattle. The feed given to livestock is field grass and beef, livestock rearing is carried out intensively, disease prevention that has been carried out is cage sanitation and treatment of intestinal worms by giving Albendazole bolus drug and in kelompok tani Hulu Gawan, injured cattle are given Gusanex Antiseptic spray. For the cattle marketing is generally through intermediary trading. The production of organic fertilizer for the Kelompok Tani  Hulu Gawan  is 2.1 tons/month with 9 livestock, Kandih Maju Bersama 1.4 tons/month with 5 livestock and Sawah Rambahan 1.7 tons/month with 7 livestock. Birth rate of cattle in the Kelompok Tani Hulu Gawan in  the number of children born was 2, Kandih Maju Bersama and Sawah Rambahan was 1 cattle. None of the cattle of the Kandih Maju Bersama and Sawah Rambahan farmer groups died, while the Kelompok Tani Hulu Gawan had 1 death. The organic fertilizer produced is processed in dried form and used for organic farm and organic rice fields. Keywords: UPPO Program Evaluation, Farmers Group, Solok District